Practice and Rituals in Uyghur Buddhist Texts: A Preliminary Appraisal - Wilkens, Jens (Dynamics in the history of religions, 2022)
Unlike in Tibetan, Chinese, or Indian Studies, ritual and practice are topics yet to be explored in detail with regard to Uyghur Buddhism. Rather, the focus in Uyghur Studies so far is on making the texts accessible in editions and translations. While some genres of Old Uyghur literature—such as confession texts and tantric materials—clearly have to be understood within the framework of Buddhist rituals, the applicability of a ritual framework is not quite as obvious for other types of texts. Uyghur Buddhist texts with a clear-cut ritual setting draw heavily on the Chinese and Tibetan traditions. This paper looks at the contexts in which a ritual framing of Uyghur literature can be established (that is, festivals, visualisations, dhāraṇīs, amulets, talismans, and so on).